Pemanfaatan Media Sosial Instagram sebagai Media Public Relations dalam Mengenalkan Employer Branding Klinik Ella - Indriana Putri Wijaya; Esfandani Peni Indreswari; Rahmat Wisudawanto (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
The increasing competition in the healthcare and beauty service industry encourages organizations to strengthen their employer branding to attract and retain qualified talent. Social media, particularly Instagram, has become an important Public Relations platform for communicating organizational values and employment opportunities to prospective employees. This study aims to analyze the Public Relations strategy implemented through the @ellacareer Instagram account in building Klinik Ella's employer branding. A descriptive qualitative approach was employed using interviews, observations, documentation, and social media content analysis as data collection techniques. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that the @ellacareer Instagram account serves as a Public Relations medium to communicate the organization's identity through job vacancy information, employee stories, organizational culture, employee development programs, and company activity documentation. These communication practices function not only to disseminate information but also to establish a positive employer image that emphasizes career development, collaboration, and employee appreciation. The study concludes that Instagram plays a significant role as a Public Relations medium in strengthening Klinik Ella's employer branding and enhancing the organization's attractiveness to prospective employees.